ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR KEWIRAUSAHAAN KELAS XI PEMASARAN DI SMK MANDIRI PONTIANAK - Zulpian, Zulpian; Sulistyarini, Sulistyarini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to determine internal factors and external factors that affect student learning difficulties in entrepreneurship subjects in class XI Marketing at Pontianak Independent Vocational School. The research method used is descriptive in the form of qualitative research. The subjects of this study were 6 students who had difficulty learning entrepreneurship and 1 entrepreneurship teacher class XI Marketing. The technique of collecting data through observation, interview and documentation techniques. The results showed that internal factors that affect students' learning difficulties in entrepreneurship subjects in class XI Marketing include impaired student health due to diseases that interfere with learning, lack of intelligence, lack of interest in entrepreneurship and lack of readiness for entrepreneurship. While external factors that affect students' learning difficulties in entrepreneurship subjects in class XI Marketing include lack of parental attention at home to children's learning due to busy work, entrepreneurial teacher teaching methods that still use lecture methods and teachers are less varied in teaching, discipline who are still lacking and friends hang out in class that often interfere when the learning process takes place. Keywords: Entrepreneurship Subjects, Factors Affecting Learning Difficulties